Modification of changes in the stress-strain state of crane slewing gear elements while operational conditions - L. A. Sladkova; V. V. Fokin (Омский научный вестник)
Despite the high technical level of hoisting equipment purchased abroad, a catastrophic failure of the slewing bearings of these cranes occurs after 3-5 years of service instead of the regulated 15 years. The most characteristic are: wear of 6-polyamide cassettes, cages of gear teeth and turntable; rolling elements falling out of the turntable; squeezing out the sealing tape. To identify the hidden cause of premature failure of the slewing rings of «Liebherr» cranes, the authors carried out the experiment during loading and unloading operations, which shows the tendency of warming up the elements of the slewing support, considering the cyclic nature of the crane operation. It has been established that this process is linear both for cassettes (polyamide 6 material), in which the rolling elements are located, and for the rolling elements themselves (bearing steel). For 5 loading cycles, the rolling elements warm up to a 40 mm depth to a temperature of about 40-45° C. The proposed working hypothesis allows identifing the hidden cause of premature failure of the slewing support of «Liebherr» cranes operating in central Russia. A change in the stress-strain state of the cassette is established, leading to an increase in wear of the cassettes and rolling elements, since stresses arise between the end of the roller surface and the cassette in the direction of the contact plane.